Feeling the past: beyond causal content - Viera, Gerardo (Estudios de Filosofía, 2021)
Memories often come with a feeling of pastness. The events we remember strike us as having occurred in our past. What accounts for this feeling of pastness? In his recent book, Memory: A self-referential account, Jordi Fernández argues that the feeling of pastness cannot be grounded in an explicit representation of the pastness of the remembered event. Instead, he argues that the feeling of pastness is grounded in the self-referential causal content of memory. In this paper, I argue that this account falls short. The representation of causal origin does not by itself ground a feeling of pastness. Instead, I argue that we can salvage the temporal localization account of the feeling of pastness by describing a form of egocentric temporal representation that avoids Fernández’s criticisms.